2020
DOI: 10.1016/j.gpb.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Gene Expression Changes are Associated with Aging in Mice

Abstract: Aging is a complex process that can be characterized by functional and cognitive decline in an individual. Aging can be assessed based on the functional capacity of vital organs and their intricate interactions with one another. Thus, the nature of aging can be described by focusing on a specific organ and an individual itself. However, to fully understand the complexity of aging, one must investigate not only a single tissue or biological process but also its complex interplay and interdependencies with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
5
27
0
Order By: Relevance
“…We observed that, based on VST-normalized gene expression values, samples tend to cluster by tissue, which is in line with what Schaum et al . [ 6 ] found, as well as with previous observations [ 5 , 7 , 15 , 20 24 ]. For this reason, subsequent analyses were performed on each tissue separately ( Figure 1A ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that, based on VST-normalized gene expression values, samples tend to cluster by tissue, which is in line with what Schaum et al . [ 6 ] found, as well as with previous observations [ 5 , 7 , 15 , 20 24 ]. For this reason, subsequent analyses were performed on each tissue separately ( Figure 1A ).…”
Section: Resultssupporting
confidence: 92%
“…Another study across 17 mouse tissues, whose dataset we re-analyzed in this work, identified shift points of gene expression trajectories at around 6 months for extracellular matrix genes, 10 months for mitochondrial genes, 12 months for genes encoding heat shock proteins, and at around 15 months for immune response genes [ 6 ]. Other studies also suggest tissue-specific turning points in gene expression profiles [ 6 , 20 , 35 ]. For example, immune response gene expression was found to change in the mouse kidney between 13 and 20 months, in line with the previously described organismal trend, whereas in the spleen and lung this shift occurs later in life, at around 26 months [ 35 ].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Even though genomic data are a useful tool for examining the genetic architecture of a given species or individual, they often do not provide information about which genes are expressed and where (i.e., which tissue/organ); the magnitude of expression; or the development stage(s) at which they are expressed. Ultimately, the generation of organspecific transcriptomes will be possible at various points in a model organism's life history, as well as under specific experimental conditions, including anti-aging interventions As the field has grown, the human aging transcriptome has been shown to be a robust tool for estimating the biological age of an individual [152], as well as measuring age-related changes in tissue-specific transcriptomes of model organisms such as monkeys [153], mice [154], D. melanogaster [155,156], C. elegans [157,158], and yeast [159]. Not surprisingly, relatively little is known about the aging transcriptome in birds, with the exception of studies of brain [160] and thymus [161] transcriptomes in populations of domestic chicken.…”
Section: Avian Transcriptomicsmentioning
confidence: 99%